THE IMPACT OF INTERNAL FACTORS ON SMALL BUSINESS SUCCESS: A CASE OF SMALL ENTERPRISES UNDER THE FELDA SCHEME - Khadijah Mohamad Radzi; Mohammad Nazri Mohd Nor; Suhana Mohezar Ali (Asian Academy of Management Journal, 2017)
This study attempts to identify the antecedents of business success in the Malaysian perspective, with particular reference to small businesses under the Federal Land Development Authority (FELDA) scheme. Cross sectional data were collected from 199 small businesses operating under the (FELDA) scheme via questionnaire. The data collected were analysed using partial least square method. The empirical results indicated that only entrepreneurial competency and technology usage are related to successes of small businesses. However, this study found insufficient empirical evidence to support the relationship between marketing capability, financial resources, knowledge sharing, and business success. As this study was confined to the small businesses under the FELDA scheme, this provides valuable findings by uncovering the differences among the critical success factors due to the different reasons for formation of the small businesses. The insights gained from this study could facilitate industry practitioners to develop comprehensive business strategies and effective institutional policies to maintain the global competitiveness of small businesses under the FELDA scheme.